The possibility of distance methods application for snow dump sites monitoring; MATEC Web of Conferences; Vol. 48 : Space Engineering - Pasko O. A. Olga Anatolievna; Makartsova E. Elena; Ushakova N. Natalia; Tokareva O. S. Olga Sergeevna; Mochalov M. Mikhail (Application of the Space Technologies in Biomedical Engineering and Environmental Monitoring, 2016)
Title screen